2017
DOI: 10.5740/jaoacint.16-0139
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Virulence Factors and Molecular Characterization of the Clonal Relations of Multidrug-Resistant Acinetobacter baumannii Isolates

Abstract: Multidrug-resistant (MDR) Acinetobacter baumannii infections are a great public health concern and demand continuous surveillance and antibiotic stewardship. Virulence traits and the pathogenicity of Acinetobacter are less studied compared with the molecular epidemiological and antibiotic resistance profile of this organism. In our present study, we investigated the primary characteristics contributing to the virulence of MDR A. baumannii isolates and compared them with avirulent isolates. A total of 32 well-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
1
16
1
Order By: Relevance
“…Additionally, biofilm formation, phospholipase C production, hemolytic activity, and toxin production are higher than in non-virulent strains. This indicates that clinically isolated ST195 strains possess high virulence [34].…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, biofilm formation, phospholipase C production, hemolytic activity, and toxin production are higher than in non-virulent strains. This indicates that clinically isolated ST195 strains possess high virulence [34].…”
Section: Discussionmentioning
confidence: 92%
“…Acinetobacter baumannii also has iron siderophores and acinetobactin, the best-characterized A. baumannii siderophore, is a mixed type siderophore with an oxazoline ring derived from threonine (McConnell et al, 2013). Acinetobactin is an A. baumannii virulence factor (Gaddy et al, 2012; Penwell et al, 2012; Megeed et al, 2016). Impaired acinetobactin biosynthesis and transport functions significantly reduce the ability of A. baumannii ATCC 19606 cells to persist within epithelial cells and cause cell damage and animal death (Gaddy et al, 2012).…”
Section: Acinetobacter Baumannii Virulence Factors and Pathogenesismentioning
confidence: 99%
“…Mutation in the entA gene, which is essential for biosynthesis of the acinetobactin precursor 2,3-dihydroxybenzoic acid, also significantly reduces the capacity of A. baumannii ATCC 19606 cells to persist within human alveolar epithelial cells and diminishes the ability to infect and kill Galleria mellonella larvae (Penwell et al, 2012). One study showed that acinetobactin production occurs significantly more frequently in MDR A. baumannii isolates than that in avirulent isolates (Megeed et al, 2016). …”
Section: Acinetobacter Baumannii Virulence Factors and Pathogenesismentioning
confidence: 99%
“…The production of the siderophore acinetobactin and its role in Fe acquisition and the virulence of LAC-4 and ATCC 19606 has been described (8,21), and acinetobactin synthesis and associated transport genes have been mapped in various isolates, including LAC-4, ATCC 17978, and ATCC 19606 (22,23). It is interesting to note in this regard that MDR isolates have been reported to typically possess the acinetobactin Fe acquisition virulence system (9).…”
Section: Discussionmentioning
confidence: 99%
“…Iron acquisition is a virulence determinant for A. baumannii with its acinetobactin iron siderophore acquisition system being more prevalent in MDR isolates (1,8,9). Gallium, a nonfunctional analogue of Fe that inhibits A. baumannii growth and biofilm formation in vitro by displacing functional iron (10,11), has also been shown to suppress A. baumannii experimental pneumonia in mice (12).…”
mentioning
confidence: 99%